DEVELOPMENT OF UNDERWATER ROV (REMOTELY OPERATED VEHICLE) SYSTEMS AND MECHANISM - Tianur, Tianur; Suswanto, Bagas Prayoga Suswanto; Hendriko, Hendriko; Rahmawaty, Made (Politeknik Negeri Sriwijaya, Indonesia, 2023)
Â Remotely Operated Vehicle or abbreviated as ROV is an underwater explorer robot where the robot is controlled remotely by an operator using a remote control system.Â Water ecosystems certainly have various kinds of hazards that cause harm to divers, such as wild animals, waters contaminated with toxic waste, limited oxygen, and many other risks. Based on these problems, research was carried out, namely the Design and Development of Underwater ROV (Remotely Operated Vehicle) Mechanisms and Systems where the tool built is an underwater robot that uses 8 DC motors to be able to perform 12 types of movements under water. The final result obtained by the ROV is that it is able to perform all of these movements except for the right somersault and left somersault. The speed and direction of rotation of the motor is controlled by a device, namely the BTS7960 motor driver. This robot aims to measure pressure and temperature and capture images underwater to a depth of 4m. Pressure and temperature measurements were made using a BMP180 pressure sensor and a DS18B20 temperature sensor where the measurement results will be displayed on a 16x2 LCD. Based on the test results, the pressure sensor has an error rate of 3.6% and a temperature sensor of 0.34%. Images and videos are captured by a device, namely a CCTV camera where the device is connected to a laptop device as a monitor. The test produced results in the form of images and videos that were quite clear.